Effects of Nigella sativa oil on Th1/Th2, cytokine balance, and improvement of asthma control in children - Wisnu Barlianto; Maria Rachmawati; Muhammad Irawan; Desy Wulandari (Indonesian Pediatric Society, 2017)
Background Asthma is a chronic inflammatory disease of the airways characterized by involvement of a variety of inflammatory cells. Asthma is associated with imbalances between Th1/Th2 cells and their characteristic cytokine profiles. Nigella sativa is a plant that possesses immunomodulatory and anti-inflammatory properties.Objective To investigate the potential anti-asthmatic effect of Nigella sativa oil on Th1/Th2 cells, IFN-É£/IL-4 cytokines, and improvement of asthma control.Methods Children aged 6-15 years with asthma in Dr. Saiful Anwar Hospital, Malang, were enrolled in this study. All patients were treated based on standard treatment guidelines for asthma. Nigella sativa oil (NSO) was given per oral as supplementary treatment at a dose of 15-30 mg/kg/day for 8 weeks, in a randomized, single-blind, controlled trial. Peripheral Th1 and Th2 cells were counted by flow cytometry and IFN-É£ and IL-4 cytokines were measured by ELISA. Improvement of asthma control was assessed by theÂ asthma control test (ACT) score.Results Twenty-eight patients completed the study, 14 in the NSO treatment group and 14 in standard treatment group. No significant differences were found in the number of Th1 and Th2 cells, or in the Th1/Th2 ratio between groups after treatment (P=0.074, P=0.481, and P=0.265, respectively). Compared to the control, the NSO group showed a significant elevation of IFN-É£ (P=0.046) and reduction of IL-4 (P=0.002). At the end of study, ACT score was not significantly different between groups (P=0.413).Conclusion Supplementation with Nigella sativa oil improves IFN-É£/IL-4 balance and asthma control in children with asthma.